2009
DOI: 10.1002/hyp.7372
|View full text |Cite
|
Sign up to set email alerts
|

Input data selection for solar radiation estimation

Abstract: Abstract:Model input data selection is a complicated process, especially for non-linear dynamic systems. The questions on which inputs should be used and how long the training data should be for model development have been hard to solve in practice. Despite the importance of this subject, there have been insufficient reports in the published literature about inter-comparison between different model input data selection techniques. In this study, several methods (i.e. the Gamma test, entropy theory, AIC (Akaike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 55 publications
0
12
0
3
Order By: Relevance
“…Studies by Remesan et al . (2008) and Ahmadi et al . (2009) also suggested that solar radiation is a difficult parameter to obtain and has a high sensitivity towards ET o estimation (Ishak et al ., 2010).…”
Section: Performance Of Hydro-meteorological Variablesmentioning
confidence: 96%
“…Studies by Remesan et al . (2008) and Ahmadi et al . (2009) also suggested that solar radiation is a difficult parameter to obtain and has a high sensitivity towards ET o estimation (Ishak et al ., 2010).…”
Section: Performance Of Hydro-meteorological Variablesmentioning
confidence: 96%
“…Zhang and Singh [50] combined copula theory with entropy theory to derive the bivariate rainfall and runoff distributions. Recently, entropy has been used as a pre-processing step for model input selection [51][52][53]. Comprehensive reviews of the use of entropy in hydrology are provided in [47,54].…”
Section: Introductionmentioning
confidence: 99%
“…To Gamma test αναφέρθηκε πρώτα από τους Stefansson et al, [1997], και αποδείχτηκε από τους Evans and Jones [2002] και έκτοτε εφαρμόστηκε σε πολλές μελέτες [Chuzhanova et al, 1998;Tsui and Jones, 1999;Goodridge et al, 2001;Tsui et al, 2002;Jones, 2004;Jones et al, 2007;Evans and Jones, 2008]. Πρόσφατα άρχισε να βρίσκει εφαρμογή και σε υδρολογικές μελέτες [Kashefipour et al, 2005;Remesan et al, 2008Remesan et al, ,2009Ahmadi et al, 2009;Moghaddamnia et al, 2009;Vasiliades and Loukas, 2010a,b]. Σε μία πρόσφατη μελέτη για τον υπολογισμό της ηλιακής ακτινοβολίας, το Gamma test συγκρίθηκε με άλλες μεθοδολογίες για την εκτίμηση των δεδομένων εισόδου [Ahmadi et al, 2009].…”
Section: ) συνδυασμός των ανωτέρω μεθόδωνunclassified
“…Πρόσφατα άρχισε να βρίσκει εφαρμογή και σε υδρολογικές μελέτες [Kashefipour et al, 2005;Remesan et al, 2008Remesan et al, ,2009Ahmadi et al, 2009;Moghaddamnia et al, 2009;Vasiliades and Loukas, 2010a,b]. Σε μία πρόσφατη μελέτη για τον υπολογισμό της ηλιακής ακτινοβολίας, το Gamma test συγκρίθηκε με άλλες μεθοδολογίες για την εκτίμηση των δεδομένων εισόδου [Ahmadi et al, 2009]. Οι μεθοδολογίες σύγκρισης ήταν οι θεωρία της εντροπίας (entropy theory) και οι τεχνικές AIC/BIC με βάση τα μη γραμμικά μοντέλα που χρησιμοποιήθηκαν για τον υπολογισμό της ηλιακής ακτινοβολίας.…”
Section: ) συνδυασμός των ανωτέρω μεθόδωνunclassified
See 1 more Smart Citation